2014
DOI: 10.1002/cne.23643
|View full text |Cite
|
Sign up to set email alerts
|

The orexinergic neurons receive synaptic input from C1 cells in rats

Abstract: The C1 cells, located in the rostral ventrolateral medulla (RVLM), are activated by pain, hypoxia, hypoglycemia, infection and hypotension and elicit cardiorespiratory stimulation, adrenaline and ACTH release, and arousal. The orexin neurons contribute to the autonomic responses to acute psychological stress. Here, using an anatomical approach, we consider whether the orexin neurons could also be contributing to the autonomic effects elicited by C1 neuron activation. Phenylethanolamine N-methyl transferase-imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 61 publications
0
28
0
3
Order By: Relevance
“…Although most CNS catecholaminergic cell groups are linked to cardiorespiratory regulation (5,18), the majority of catecholamine inputs to PVN arise from VLM and nTS (9,44,52). Catecholaminergic VLM neurons project heavily to and influence magnocellular vasopressinergic and oxytocinergic neurons and parvocellular CRH neurons in the PVN (10,52,55), suggesting a role in neuroendocrine function.…”
Section: R725mentioning
confidence: 99%
See 1 more Smart Citation
“…Although most CNS catecholaminergic cell groups are linked to cardiorespiratory regulation (5,18), the majority of catecholamine inputs to PVN arise from VLM and nTS (9,44,52). Catecholaminergic VLM neurons project heavily to and influence magnocellular vasopressinergic and oxytocinergic neurons and parvocellular CRH neurons in the PVN (10,52,55), suggesting a role in neuroendocrine function.…”
Section: R725mentioning
confidence: 99%
“…The nTS receives and integrates a variety of visceral inputs, including from chemoafferents, and has reciprocal projections to cardiorespiratory brain regions in addition to PVN (1,40). VLM C1 neurons also have multiple projections to cardiorespiratory regions and influence breathing (5,6,18). Thus, catecholaminergic inputs from VLM likely contribute to neuroendocrine responses to hypoxia, whereas both nTS and VLM may play a role in chemoreflex-mediated increases in ventilation.…”
Section: R725mentioning
confidence: 99%
“…One recent study demonstrated that C1 neurons of the rostral ventrolateral medulla, which are intrinsically hypoxia-sensitive neurons, have afferent inputs to the orexinergic neurons (Bochorishvili et al, 2014). C1 neurons respond to severe reductions in brain PaO 2 (Sun and Reis, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of C1 neurons express Fos protein in conscious mammals exposed to hypoxia (Erickson and Millhorn, 1994), and sympathetic nerve activation elicited by carotid body stimulation is severely depressed after selective lesions of these cells (Schreihofer and Guyenet, 2000). The C1 neurons establish asymmetric synapses with orexinimmunoreactive cell bodies or dendrites (Bochorishvili et al, 2014). Anterograde tracing with viral vectors has revealed C1 cell projections to the lateral hypothalamus (Bochorishvili et al, 2014); the rostral ventrolateral medulla may be a key nucleus regulating both descending presympathetic neurons and afferents projections to orexin nuclei to activate state-dependent control of sympathetic responses to hypoxia (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation